Theoretical-Methodological Foundations of the Management of Natural Monopolies - Samieva Maftuna (Journal of Artificial Intelligence and Digital Economy, 2024)
This scientific article covers theoretical methodological aspects in the regulation and management of the spheres of natural monopolies. The reasons for the origin of natural monopolies, their negative consequences in the economy are covered. Proposals and recommendations have been developed on the economic features of the regulation of natural monopolies.